2015
DOI: 10.1007/s10815-015-0534-y
|View full text |Cite
|
Sign up to set email alerts
|

Morphokinetic parameters using time-lapse technology and day 5 embryo quality: a prospective cohort study

Abstract: The identified morphokinetic parameters and their cutoffs, albeit of limited clinical value, add to the increasing knowledge concerning the potential predictive markers of a top-quality blastocyst. Additional evidence is necessary before validated time-lapse parameters can be used for embryo selection in IVF laboratories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…Combining time-lapse imaging with comparative genomic hybridization (CGH), Chawla et al found that some significant morphokinetic parameters can be used as markers to predict aneuploidies [19]. Meanwhile, different assessment assays and statistical models were applied to refine the morphokinetic variables and increase the chance of predicting a top-quality blastocyst [20]. However, considering the potential technical and statistical error in time-lapse imaging, one should be cautious in overinterpreting the results [21][22][23][24].…”
Section: Bf Samplingmentioning
confidence: 99%
“…Combining time-lapse imaging with comparative genomic hybridization (CGH), Chawla et al found that some significant morphokinetic parameters can be used as markers to predict aneuploidies [19]. Meanwhile, different assessment assays and statistical models were applied to refine the morphokinetic variables and increase the chance of predicting a top-quality blastocyst [20]. However, considering the potential technical and statistical error in time-lapse imaging, one should be cautious in overinterpreting the results [21][22][23][24].…”
Section: Bf Samplingmentioning
confidence: 99%
“…In mouse embryos the first mitosis lasts for 90–120 min, whereas the second lasts only 60–80 min 16 , 17 . The human first embryonic mitosis is also very long (approximately 2,5–3hrs 20 24 ), and although there are no published data on the length of the second embryonic mitosis, some observations confirm that it tends to be markedly shorter (R. Milewski, J. Czerniecki, S. Wołczyński, unpublished data). By comparison, in somatic cells the length of M-phase varies between 30 and 60 min, depending on the cell type and on the length of the SAC-regulated prometaphase, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative evaluation of embryo characteristics with digital imaging systems has become an active research area 9,10 , and efforts have been made to improve objectivity during the embryo selection process by combining multiple morphological parameters and morphokinetic analysis in mathematical models, aiming to generate predictive capabilities for development potential and implantation. Such models, however, are often limited to initial development stages of the embryo, dependent on currently existing classifications, or require sophisticated time-lapse microscopy systems [11][12][13][14] .…”
mentioning
confidence: 99%